Meningkatkan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Agama Katolik Melalui Model Problem Based Learning (PBL) di SMP Negeri 2 Panombeian Panei - Mei Endang Situmorang (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
A teacher certainly needs methods to convey learning materials so that the materials can be quickly understood by the students. The purpose of this research is to determine the improvement in learning outcomes of seventh-grade students at SMP Negeri 2 Panombeian Panei. This research is designed to enhance student learning activity using the Problem-Based Learning model, which emphasizes how active students are in being independent and skilled at SMP Negeri 2 Panombeian Panei. The learning activity referred to in this study is physical activity and mental activity. The type of research is Classroom Action Research (CAR), where the teacher acts as the implementer of the learning while the researcher acts as the observer. This research was conducted in the odd semester of the 2024/2025 academic year, specifically in September. The subject of this research is the seventh-grade students of SMP Negeri 2 Panombeian Panei, with a total of 8 participants. The object of the research is the students' learning activity. The data collection technique uses observation and interviews. Data is analyzed descriptively and presented in the form of tables and graphs. The research results show an increase in student learning activity, with a 25% improvement in Cycle I (newly developing category), and then a 75% increase in Cycle II (good category).